Pengolahan Ikan Lemadang Menjadi Abon dan Ikan Asap di Desa Songbanyu Daerah Istimewa Yogyakarta - Ekaristianto, Felix Brian Hari (Jurnal Atma Inovasia, 2023)
Desa Songbanyu is famous for its marine and fisheries midwives because it is directly adjacent to the sea. As a result, our team intends to contribute by making processed food products sourced from marine fisheries in a desire to help the economic growth of rural communities. Of course there are stages so that the product can be maximally successful, such as the processing and marketing that will be carried out. The products that will be made are Fish Shredded and Smoked Fish, both of which come from the original lemadang fish. The method that will be applied is descriptive qualitative by referring to various literatures and literature reading materials. The results and discussion created from the writing carried out by the writing team is to tell how to manage or make lemadang fish so that it can become shredded fish and smoked fish correctly and well. Then the discussion of the marketing strategy used is the direct technique and WOM or in other words Word of Mouth because it is relatively easy to do and cuts costs. Thus, in terms of products that are good and tasteful to the use of appropriate marketing strategies and easy to covet culinary products from processed lemadang fish can be a good business idea for the people of Desa Songbanyu in supporting the economy towards a better direction.